Recent Management of Patients with Advanced Epidermal Growth Factor Receptor Mutation Non-small Cell Lung Cancer: Role of Afatinib and Lesson Learned for Developing Countries - Zulkifli Amin; Vito Filbert Jayalie; Wulyo Rajabto (Acta Medica Indonesiana, 2017)
Lung cancer is a devastating disease with a high incidence, mortality and morbidity rate, especially in developing countries. Conventional treatment with cytotoxic chemotherapy has some limitations attributed to chemoresistance and toxicity. Recent advances have shown that first generation Tyrosine Kinase Inhibitor (TKI), Gefitinib and Erlotinib, and the newest available second generation Tyrosine Kinase Inhibitor (TKI), Afatinib, have the potential to be an option in the management of patients with epidermal growth factor receptor/ EGFR mutation positive advanced/ metastatic non-small cell lung cancer. Afatinib works by binding to EGFR irreversibly, thus inactivating the tyrosine kinase receptor. Some studies demostrated that Afatinib first-line may result in longer progression free survival (PFS) and better disease control, and as an alternative for patients who intolerance to Gefitinib or Erlotinib. In Indonesia, the era of National Health Insurance has been implemented and National Health Insurance has covered treatment for cancer, including first generation TKIs, Gefitinib dan erlotinib, for patients with EGFR mutation positive advanced/ metastatic non-small cell lung cancer at Cipto Mangunkusumo National Hospital. Afatinib, as one of the newest available second generation TKI, may be given free of charge too as an alternative if the National Health Insurance will be covered in the future. Further research is needed to know the efficacy and adverse effects that may occur in patients from developing countries.